Arthropod larvae misidentified as parasitic worm infection. (28th October 2011) - Munisamy, Sreetharan; Kilner, Rachael
Abstract : A healthy, asymptomatic man living in London, presented with seeing 'worms' in his toilet for two successive summer seasons. Repeated microscopic examination and cultures of both his faeces and urine were normal. He was empirically treated with multiple courses of antihelminthics without resolution of this problem. A sample of the worms was obtained, and positively identified as arthropod larvae under microscopic examination. These larvae do not parasitically colonise humans. It was subsequently deduced that a flying arthropod (most likely Culex pipiens mosquito) had laid eggs in standing toilet water, and the hatched larvae had been mistaken for parasitic worms. The patient was declared free of parasites and remains healthy. This case illustrates the dangers of starting empirical treatment without positive confirmation of causative organisms, which can result in unnecessary and potentially harmful treatment.